Peranan Guru Pendidikan Agama Islam Untuk Mengatasi Kesulitan Belajar Pada Peserta Didik Di SD Negeri 05 Bermani Ilir - Doli Mukhti Siregar; Maria Bofitar (GHAITSA : Islamic Education Journal, 2024)
This research is based on the role of Islamic religious education teachers in overcoming learning difficulties of students at SD Negeri 05 Bermani Ilir. The purpose of this study is to determine the supporting factors and inhibiting factors of the role of Islamic religious education teachers in overcoming learning difficulties. The theory used in this study is qualitative with data collection through observation, interviews and documentation. The results obtained from this study are that teachers have played a good role with teachers who are guided to become facilitators and make their students like their own children. By approaching their students, teachers become role models for their students.